Hartz IV and the Decline of German Unemployment: A Macroeconomic Evaluation - Brigitte Hochmuth; Britta Kohlbrecher; Christian Merkl; Hermann Gartner (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper proposes a new approach to evaluate the macroeconomic effects of the Hartz IV reform in Germany, which reduced the generosity of long-term unemployment benefits. We use a model with different unemployment durations, where the reform initiates both a partial effect and an equilibrium effect. The relative importance of these two effects and the size of the partial effect are estimated based on the IAB Job Vacancy Survey. Our novel methodology provides a solution for the existing disagreement in the macroeconomic literature on the unemployment effects of Hartz IV. We find that Hartz IV was a major driver for the decline of Germany's unemployment and that partial and equilibrium effect where of equal importance. We thereby contribute to the literature on partial and equilibrium effects of unemployment benefit changes. In addition, we are the first to provide direct empirical evidence on labour selection, which can be interpreted as one dimension of recruiting intensity.
Keywords: E24; E00; E60; 330; Unemployment benefits reform; search and matching; Hartz reforms